1984
DOI: 10.1148/radiology.153.3.6093190
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the lymph nodes: comparison with CT.

Abstract: This retrospective study of 144 patients was made to (a) assess the potential of magnetic resonance (MR) for demonstrating lymph nodes using spin-echo technique, (b) compare the MR results with those of CT, and (c) determine the optimal pulse-sequence interval (TR) and echo-delay time (TE) for imaging lymph nodes. The reported CT findings on normal lymph nodes were compared with MR findings in 60 patients who underwent MR imaging of the neck (20 patients), chest (20 patients), abdomen (10 patients), and pelvis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
2

Year Published

1986
1986
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(38 citation statements)
references
References 0 publications
0
35
1
2
Order By: Relevance
“…In bladder cancer, tumor metastases in regional lymph nodes cannot be detected by CT or pedal lymphangiography in 30–40% of the patients. MRI was found to be more sensitive than CT; the minimum size of detectable lymph nodes was observed to range between 7 and 11 mm [4, 5, 6]. Similar findings have been reported for the detection of lymph node metastases by CT and MRI in prostate cancer [6, 7].…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In bladder cancer, tumor metastases in regional lymph nodes cannot be detected by CT or pedal lymphangiography in 30–40% of the patients. MRI was found to be more sensitive than CT; the minimum size of detectable lymph nodes was observed to range between 7 and 11 mm [4, 5, 6]. Similar findings have been reported for the detection of lymph node metastases by CT and MRI in prostate cancer [6, 7].…”
Section: Discussionmentioning
confidence: 54%
“…MRI was found to be more sensitive than CT; the minimum size of detectable lymph nodes was observed to range between 7 and 11 mm [4, 5, 6]. Similar findings have been reported for the detection of lymph node metastases by CT and MRI in prostate cancer [6, 7]. Due to the low accuracy of conventional imaging methods, selection of the appropriate therapy is based on histopathological examination of pelvic lymph nodes dissected by pelvic lymphadenectomy.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These imaging modalities are also useful for the postoperative evaluation of the residual lymph nodes. However, small lymph node metastases less than 1 cm in diameter cannot be detected by MRI or CT [7].…”
Section: B Amentioning
confidence: 99%
“…Russell et al, in 1992, reported for the first time on the value of pelvic MRI in designing the lateral fields of the box technique [5] . MRI offers the possibility of visualising the anatomy of the pelvis on all planes and enables much better evaluation of soft tissue structures and tumour depiction than CT [11][12][13][14][15][16] . Russell [3,6,7] .…”
Section: Figurementioning
confidence: 99%